Customer’s Perception on the Safety and Hygiene Level of Keropok Lekor and Keropok Keping at Kampung Losong, Terengganu - RADEN ISMAIL, RADEN MOHD FARHAN HELMY; AB RAHMAN, NURUL LATIFAH AMALIAH; ROHIAT, MOHD AKMAL (Research and Innovation in Technical and Vocational Education and Training, 2021)
Safety and hygiene in the handling and preparation of food is one of the key factors in ensuring that the food provided is safe to eat. Therefore, this study was conducted to determine the customer’s perception on the safety and hygiene of the keropok lekor and keropok keping process in Kampung Losong, Terengganu. In this study, the researchers focused on several aspects, namely the safety of the premises and the safety of the food operator and the hygiene of the workers. For data analysis the researcher has chosen to use the questionnaire form method. The findings of this study were analyzed using Statistical Package for The Social Science (SPSS) version 25. Computer analysis data showed a mean value of 3.94 for the safety of the premises and food operators. Meanwhile, 3.92 (High) for personal hygiene of employees.